Examining Relationship of Knowledge Sharing, Innovation Capability, Responsive Capability and Marketing Performance in Inkubator Bisnis at UPN “Veteran”East Java - L. Nirawati; R. R. Prayogo (Nusantara Science and Technology Proceedings)
Business organizations are required to be able to do effective marketing. Market change demands a business organization to have a marketing capability in innovation and respond to in making a product to be competitive so that creating a quality product. Creating a quality product is influenced by the knowledge of the product to be created so as to produce good marketing performance. The purpose of this study is to see how big influence towards knowledge sharing innovation capability, the capability to respond to the market and performance marketing. A questionnaire was given to students who are in the university environment by using purposive sampling with limited and specific respondents on students who have a business on Incubator business. Reliability and validity of measured through the median and variation analysis of Cronbach's alpha, Analysis using SEM model structure with SmartPLS used to test the relationship between research variables using 100 respondents. The results showed that sharing knowledge is a positive and significant effect on the capabilities of innovation and responsive capabilities, but insignificant effect on performance marketing. The responsive capability of innovation and capability can affect the performance of marketing in a positive and significant.